A proposal to expand the classification of obesity according to body mass index (BMI) for patients referred for bariatric surgery - Wyleżoł, Mariusz; Gaździńska, Agata; Kaniewska, Ewelina; Mojkowska, Aleksandra (Lekarz POZ, 2016)
Obesity is today one of the most important and, at the same time, the most neglected health problem in the world. The body mass index (BMI) is commonly used to determine the stage of obesity. In the current classification, there are three stages of obesity: grade I, II and III. The increasing incidence of people suffering from morbid obesity and super morbid obesity means that the traditional three-stage classification of obesity has proven to be not precise enough in the practice of bariatric surgery. We propose an expanded, more detailed classification of obesity, based on the knowledge that the risk of complications of obesity increases together with an increase of BMI. The proposed expanded scale of assessment of super morbid obesity, according to BMI, makes it possible to diagnose the severity of the disease more precisely, and, at the same time, to assess the risk of complications developing further and the risk of complications arising following bariatric surgery. The introduction of the expanded classification of BMI into clinical practice would enable a more accurate description and classification of patients referred for surgical treatment of obesity.